Development of EMG-Triggered Functional Electrical Stimulation Device for Upper Extremity Bilateral Movement Training in Stroke Patients: Feasibility and Pilot study - Song, Changho; Seo, Dong-kwon (Physical therapy rehabilitation science, 2021)
Objective: Bilateral movement training is an effective method for upper extremity rehabilitation of stroke. An approach to induce bilateral movement through functional electrical stimulation is attempted. The purpose of this study is to develop an EMG-triggered functional electrical stimulation device for upper extremity bilateral movement training in stroke patients and test its feasibility. Design: Feasibility and Pilot study design. Methods: We assessed muscle activation and kinematic data of the affected and unaffected upper extremities of a stroke patient during wrist flexion and extension with and without the device. Wireless EMG was used to evaluate muscle activity, and 12 3D infrared cameras were used to evaluate kinematic data. Results: We developed an EMG-triggered functional electrical stimulation device to enable bilateral arm training in stroke patients. A system for controlling functional electrical stimulation with signals received through a 2-channel EMG sensor was developed. The device consists of an EMG sensing unit, a functional electrical stimulation unit, and a control unit. There was asymmetry of movement between the two sides during wrist flexion and extension. With the device, the asymmetry was lowest at 60% of the threshold of the unaffected side. Conclusions: In this study, we developed an EMG-triggered FES device, and the pilot study result showed that the device reduces asymmetry.